How can we drive sustainability transitions?. Issue 3 (3rd July 2022) - Mintrom, Michael; Rogers, Briony C.
Abstract: Sustainability transitions are required to address challenges of climate change, economic development, ecological integrity, and social justice. Driving sustainability transitions is difficult but necessary work. We discuss sustainability challenges and the need for transitions, with a focus on the vital roles that change agents can play. These change agents exhibit a desire to make change happen. They encourage others to join them in their efforts. After discussing the work of change agents in driving sustainability transitions, we present a case study of change in Perth, Australia, where change agents have attained considerable success in placing that city on a path toward sustainable water management practices. We suggest sustainability transitions can be effectively enabled when change agents: (1) Clarify the problem and articulate a clear vision; (2) Engage others to identify workable solutions and implementation pathways; (3) Secure support from influential stakeholders; (4) Establish effective monitoring tools and learning systems; (5) Foster long-term relationships of trust and mutual support; and (6) Develop narratives that support on-going action.